2009
DOI: 10.1177/0960327109106438
|View full text |Cite
|
Sign up to set email alerts
|

Toxicology and biodistribution study of CIGB-230, a DNA vaccine against hepatitis C virus

Abstract: CIGB-230, a mixture of a DNA plasmid expressing hepatitis C virus (HCV) structural antigens and a HCV recombinant capsid protein, has demonstrated to elicit strong immune responses in animals. The present study evaluated the plasmid biodistribution after the administration of CIGB-230 in mice, as well as toxicity of this vaccine candidate in rats. In the biodistribution study, mice received single or repeated intramuscular injections of CIGB-230, 50 μg of plasmid DNA mixed with 5 μg of Co.120 protein.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…In the case of CIGB-230, as previously described (Bacardí et al, 2009), no toxic effects were found after repeated intramuscular injection in Sprague-Dawley rats. The study was conformed by 6 groups: a non-treated group, a placebo one, a satellite group and three groups treated with 5, 15 and 50 times the planned therapeutic dose, respectively.…”
Section: Studies Of Toxicity To Repeated Dosesupporting
confidence: 58%
See 3 more Smart Citations
“…In the case of CIGB-230, as previously described (Bacardí et al, 2009), no toxic effects were found after repeated intramuscular injection in Sprague-Dawley rats. The study was conformed by 6 groups: a non-treated group, a placebo one, a satellite group and three groups treated with 5, 15 and 50 times the planned therapeutic dose, respectively.…”
Section: Studies Of Toxicity To Repeated Dosesupporting
confidence: 58%
“…At the site of administration, most rats showed minimum focal infiltrate of lymphocytes and histiocytes. In the satellite group (VI), the reversion of this finding was observed, because it was present in only four of the animals (Bacardí et al, 2009). …”
Section: Studies Of Toxicity To Repeated Dosementioning
confidence: 88%
See 2 more Smart Citations
“…During the efforts to prove the safety of plasmid DNA, the biodistribution of plasmids has been studied in several animal species, and the results from published experiments all indicate that the plasmid is rapidly cleared from the body (Table 1 [1][2][3][4][5][6][7][8][9][10][11]). Directly after injection into skin or muscle, low levels of plasmids are transported via the blood stream and can therefore often be detected in various organs at early time points 0264-410X/$ -see front matter © 2010 Elsevier Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%